Corrosion Rate of Carbon Steel For Flowline and Pipeline as Transmission Pipe in Natural Gas Production with Co2 Content - Rustandi, Andi; Adyutatama, Muhammad; Fadly, Enriko; Subekti, Norman (UI Scholars Hub, 2012)
The purpose of this research is to investigate the corrosion rate of carbon steel as flowline and pipeline in natural gas production with CO2 content. The influence of variety of conditions that represent the actual conditions in practice such as CO2 partial pressure and solution composition, particularly NaCl percentage were performed. Research conducted by polarization test and simulation methods using PREDICTTM software. The result of this research is used to illustrate the level of corrosion rate of typical carbon steel i.e. API 5L X-52 occurred in natural gas pipelines due to the effect of dissolved CO2. From the experiments obtained that corrosion rate of steel in environments containing CO2 ranged between 15-28 mpy. This high corrosion rate observed could severely damage natural gas transmission flowline and pipeline. The result of this research is the first step, as an input for prevention efforts, to prevent leakage of flowline and pipeline due to corrosion of CO2 which appropriate with the lifetime that has been designed.